PENGARUH LOKASI USAHA TERHADAP PENDAPATAN USAHA DAGANG DI KECAMATAN GOMO - Ibertina Zebua (Universitas Nias Raya, 2023)
The purpose of this study was to determine the effect of business location on trading business income in Gomo District. The type of research used is a causal quantitative type. The types of data used in this study are quantitative and qualitative data types, the data sources used in this study are primary data and secondary data, with a population and sample in this study of 34 businesses. Data collection techniques are questionnaire techniques and documentation techniques. Based on the research results of testing the hypothesis with a tcount value of 7,634> ttable 1,694, it means that there is an influence of business location on the success of trading businesses in Gomo District. This study can be concluded that there is an influence of business location on trading business income in Gomo District. The suggestions for this research are (1) Entrepreneurs who want to open a business engaged in retail should be more careful in choosing a location. (2) entrepreneurs are able to occupy booths in business locations in developing their businesses. Having a good business location will enable them to increase their sales volume and turnover so that they are able to achieve business success.